FAKTOR PENENTU PERMINTAAN RUMAH TINGGAL DI PROVINSI DAERAH ISTIMEWA YOGYAKARTA - Ayuningtyas, Fitri Juniwati; Astuti, Ismadiyanti Purwaning (Jurnal Ekonomi & Studi Pembangunan, 2018)
Housing is a basic human need that must be obtained, in addition to the need for food and clothing. As the growing population and the number of household increases, it will lead to an increase in the need for new housings that continue to increase from year to year. The research focused on analysis the macroeconomic factors such as the market price of the property and real estate in Indonesia (IHPR), loan interest rate, and households in effect on the housing demand during the years 2007-2016. This study uses the secondary data from Bank Indonesia and Badan Pusat Statistik and analyzed using Ordinary Least Square (OLS). The result showed that IHPR has negative and significant effect on housing demand and the number of household has positive and significant effect on housing demand in D.I. Yogyakarta. While interest rate on loan has no effect on housing demand in D.I. Yogyakarta